Species of the genus Allothrips (Thysanoptera, Idolothripinae) from Southeast Asia, with one new species from Yunnan, China - Mound, Laurence; Zhang, Hongrui (Zootaxa, 2020)
The new species of Phlaeothripidae described here was found breeding in the leaf litter under five unrelated tree species of the plant families Cupressaceae, Lauraceae, Magnoliaceae, Myrtaceae and Pinaceae at the Kunming City Arboretum, Yunnan, China. Species of the genus Allothrips feed on the spores of fungi on the surface of dead leaves and dead wood, and the adults are usually wingless (Mound 1972). A total of 24 taxa are currently listed within this genus, and bibliographic details for each of these is available on ThripsWiki (2019). In a revision of the genus worldwide, Mound (1972) recognized only four species, but with eight subspecies in the Eurasian pillichellus, and six subspecies in the North American megacephalus. Three of the subspecies of megacephalus were described from Australia, but were presumed to have been imported by human trading across the Pacific Ocean. Subsequently, Okajima and Urushihara (1997) described expansus from Thailand as a further subspecies of megacephalus.